2015
DOI: 10.1080/01402382.2014.990694
|View full text |Cite
|
Sign up to set email alerts
|

National Parliaments and the Eurozone Crisis: Taking Ownership in Difficult Times?

Abstract: The eurozone crisis suggests a significant reinforcement of the executive dominance in EU policy-making. Opaque emergency decisions taken at European summits as well as treaties established outside of the EU legal framework facilitate the side-lining of democratically elected chambers. This development entails the risk of a new wave of deparliamentarisation in EU policy-making. An effective scrutiny of the crisis management by national parliaments is, however, indispensable to take national ownership of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 39 publications
2
40
0
Order By: Relevance
“…On the other activities, in contrast, EMU integration had no effect. This reflects the results of Auel and Höing (2015) who found that the crisis had a great impact on plenary debates, especially in donor countries, while the crisis management was dealt with more as 'business as usual' regarding resolutions or political Dialogue opinions.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…On the other activities, in contrast, EMU integration had no effect. This reflects the results of Auel and Höing (2015) who found that the crisis had a great impact on plenary debates, especially in donor countries, while the crisis management was dealt with more as 'business as usual' regarding resolutions or political Dialogue opinions.…”
Section: Resultssupporting
confidence: 62%
“…Finally, the politicisation of EU affairs through the eurozone crisis (see, for example, Puntscher Riekmann and Wydra 2013) also seems to have had an impact, especially on the debating activity of national parliaments: while crisis-related parliamentary statements accounted for only little over 10 per cent of all statements on EU matters on average, debates on crisis-related issues made up over 40 per cent of all EU debates (Auel and Höing 2015). We therefore also expect the level of EMU integration to have an impact on plenary debates.…”
Section: Himentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies suggest that especially the eurozone crisis had a rather strong effect in terms of parliamentary communication. Auel and Höing (2015), for example, conclude that the crisis had a considerable impact on plenary debates between 2010 and 2012: across all 27 national parliaments of the EU, on average more than 40 per cent of all EU debates focused on crisis-related issues. Studies have also found an increased politicisation of the EU in the plenaries due to the crisis, although the findings differ with regard to the lines along which polarisation took place.…”
Section: Beyond Scrutiny: Communication Of Eu Affairsmentioning
confidence: 99%
“…Besides, studying the parliamentary questions asked in the French Assemblée Nationale, Navarro and Brouard (2014) report that the overall proportion of EU-related questions directed at the French government was in decline at least until 2007. However, those who study a more recent time period show that parliamentary communication of EU affairs has been increasing over time (Rauh, 2015) and particularly as a result of the eurozone crisis (Auel & Höing, 2015;Puntscher Riekmann & Wydra, 2013;Wendler, 2014).…”
Section: Literature: Parliamentary Communication Of Eu Affairsmentioning
confidence: 99%